Industrial Climate Neutrality in the EU: Outline of an Integrated Industrial Green Deal - Tomas Wyns; Gauri Khandekar (Intereconomics, 2019)
Industry, and in particular the energy-intensive extraction and production of basic materials such as chemicals, cement, steel, non-ferrous metals, ceramics, and so on, is responsible for approximately 50% of global greenhouse gas emissions. If EU industry makes a successful low-carbon transition, it can be a model for other regions proving that there are numerous pathways which can help reconcile a climate-neutral society with the large consumption of materials
Keywords: 330